Microdeletion associated with the integration process of hepatitis B virus DNA. - Nakamura, T (1988)
Hepatitis B virus (HBV) DNA is often found in integrated form in hepatocellular carcinomas (HCC) and in non-cancerous liver cells of chronic carriers of HBV. However, the process of integration has not been well understood. Analyses of integrant DNA was expected to give clues. However, the majority of the integrants are products of multistep rearrangements following integrations, and analysis of randomly selected samples do not give clues for understanding the process of primary integrant formation. Therefore, one must select an appropriate integrant(s) that has a simple structure. We surveyed a collection of integrants prepared from many HCC's, and found one integrant that has the simplest structure so far studied: The viral genome is almost complete, is joined to cellular DNA using the cohesive end of the viral DNA, and furthermore, the "left" and "right" flanking cellular DNA's are almost contiguous. Analysis of the unoccupied sites in cellular DNA showed that, although almost contiguous, it has generated a microdeletion (15 base pairs) in the target sequence. This target sequence has a short region of homology to the sequence in the viral genome located close to the junction. One integrant with strikingly similar features has been reported independently. Two similar, but not identical cases from literatures could be added to this category. Therefore, the integrants with these properties may represent a unique category among those prepared from hepatocellular carcinomas. Based on these findings, we propose that this integrant represents the primary product of integration, and discuss the intermediate acting in the process of integration.